Enhancing auditor’s fraud risk assessment competency through forensic accounting training / Mohamad Mahsun - Mahsun, Mohamad (2022)
The Fraud Risk Assessment (FRA) plays a significant role in any financial audit activities of any organisation. The auditor’s opinion may influence organisations in various aspects, such as decision-making, performing financial transactions, and organisational culture. Therefore, auditors in Indonesia must follow the technical guidance and applicable audit standards on FRA. Generally, this study aims to investigate FRA practice at the Supreme Audit Board (SAB) of the Republic of Indonesia, the challenges faced by the auditors in carrying out FRA, the impact of auditor’s competency in preparing FRA, and the roles of professional training in FRA Processes. This study determined the sample purposively. Data was collected through interviews with auditors, focus group discussions with training institution staff and trainers, curriculum and other documentation, and non-participatory observation. This study found that SAB auditors did not conduct FRA at the audit planning stage because they lacked understanding in preparing the Fraud Risk Assessment Matrix (FRAM). Other challenges in implementing FRA is time pressure and financial budget. They have to finish annual financial statement audit within only 2 (two) months. Also, their budgets and human resources are limited. Furthermore, this study found that auditors with forensic accounting education backgrounds performed better FRA than those who did not. It was also found that the Supreme Audit Board Training Centre, known as Badan Pendidikan dan Pelatihan (Badiklat) SAB, did not provide training on preparing the FRAM. Badiklat SAB also has no forensic accounting curriculum to develop auditor’s technical and investigative skills, including non-financial measurement. They also did not have trainers/educators with forensic accounting education qualifications. Practically and theoretically, this study contributes to the auditor’s forensic accounting competency development. This study leads to another in-depth study of several critical processes identified for fraud prevention and detection practices— for example, education issues about fraud, anti-fraud systems, and forensic accounting techniques in auditing. Future research can investigate the relationship between FRA practices and investigative audits with forensic accounting knowledge variables as moderating